2014
DOI: 10.1111/jam.12436
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antimycotoxigenic metabolites in Anacardiaceae species from northwest Argentina: isolation, identification and potential for control of Fusarium species

Abstract: Aims: The purpose of this research was to identify antifungal compounds from leaves of Schinus and Schinopsis species useful for the control of toxigenic Fusarium species responsible of ear rot diseases. Methods and Results: Leaves of Schinopsis (S. lorentzii and S. haenkeana) and Schinus (S. areira, S. gracilipes and S. fasciculatus) were sequentially extracted with dichloromethane, ethyl acetate and methanol. The antifungal activity of the fraction soluble in methanol of these extracts (fCH 2 Cl 2 , fAcEt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Previous studies using plant extracts with antifungal activity they found that also has antimycotoxigenica activity (Aristimuño Ficoseco et al . ). In this regard, it would have been expected that extracts of P. quadrangularis present a similar effect.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies using plant extracts with antifungal activity they found that also has antimycotoxigenica activity (Aristimuño Ficoseco et al . ). In this regard, it would have been expected that extracts of P. quadrangularis present a similar effect.…”
Section: Resultsmentioning
confidence: 97%
“…The ground dry plant material was sequentially macerated in hexane (Hx), DCM, EtOAc and MeOH (100 ml each) at room temperature in total darkness for 24 h; were filtered, dried under reduced pressure at 40°C and weighed (Aristimuño Ficoseco et al . ; Babajide et al . ).…”
Section: Methodsmentioning
confidence: 96%
“…The inhibitory effect of urushiols at the level of mitochondrial respiration may represent a critical defense system in plants belonging to the Anacardiaceae family to avoid herbivorous predators and pathogenic fungi [54,55]. It is noteworthy that Rodentia, being the order with the most mammalian species, including rats and mice, lacks CD1a and almost all group 2 lipid-presenting molecules [9,10], suggesting an advantageous characteristic for them, perhaps expanding their sources of food.…”
Section: Discussionmentioning
confidence: 99%
“…Retention index of each identified compound was calculated in relation to n ‐alkanes (Aristimuño Ficoseco et al . 2014).…”
Section: Methodsmentioning
confidence: 99%